2014
DOI: 10.1007/s13277-014-1749-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on cancer-related fatigue in breast cancer patients receiving chemotherapy: a meta-analysis

Abstract: Increasing scientific evidences suggest that aerobic exercise may improve cancer-related fatigue in breast cancer patients, but many existing studies have yielded inconclusive results. This meta-analysis aimed to derive a more precise estimation of the effects of aerobic exercise on cancer-related fatigue in breast cancer patients receiving chemotherapy. The PubMed, CISCOM, CINAHL, Web of Science, Google Scholar, EBSCO, Cochrane Library, and CBM databases were searched from inception through July 1, 2013 witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 42 publications
2
64
0
4
Order By: Relevance
“…One low GRADE meta-analysis65 including only studies investigating aerobic exercise reported a pooled effect estimate for cancer-related fatigue (SMD: −0.82, 95% CI −1.04 to –0.60) that tended to be larger than the remaining meta-analyses (median SMD: −0.31; 25th percentile: −0.46; 75th percentile: −0.21), which included a mix of resistance and aerobic exercise studies. However, the other moderate GRADE meta-analysis58 that included only studies investigating aerobic exercise reported a pooled effect estimate (SMD: −0.22, 95% CI −0.39 to –0.04) that was similar to the remaining studies.…”
Section: Resultsmentioning
confidence: 99%
“…One low GRADE meta-analysis65 including only studies investigating aerobic exercise reported a pooled effect estimate for cancer-related fatigue (SMD: −0.82, 95% CI −1.04 to –0.60) that tended to be larger than the remaining meta-analyses (median SMD: −0.31; 25th percentile: −0.46; 75th percentile: −0.21), which included a mix of resistance and aerobic exercise studies. However, the other moderate GRADE meta-analysis58 that included only studies investigating aerobic exercise reported a pooled effect estimate (SMD: −0.22, 95% CI −0.39 to –0.04) that was similar to the remaining studies.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, in breast cancer survivors, IL6 has been associated with symptoms of fatigue, the most common and devastating complaint among cancer survivors (30,31), and a strong body of evidence has demonstrated that exercise improves fatigue in people with breast cancer specifically (32,33) and in people with cancer generally (34, 35). Therefore, the results of our meta-analysis lead us to hypothesize that exercise improves fatigue by counteracting key mediators of low-grade inflammation in women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity (PA) has become an important complementary treatment strategy in several chronic diseases, including coronary heart disease, metabolic syndrome, heart failure, breast cancer, and depression [14,15,16,17,18]. However, PA as a therapeutic option for IBD has not been studied sufficiently, and little is known about the effect of regular PA on disease activity, inflammation, and quality of life [19].…”
Section: Introductionmentioning
confidence: 99%